Synthesis of biologically decomposable terpolymer nanocapsules and higher-order nanoassemblies using RCMP-PISA - Sarkar, Jit (2022)
Terpolymers are used to generate bio-decomposable self-assemblies. PEG-PVL-PGMA terpolymers are synthesized via a combination of organocatalyzed living radical polymerization (RCMP) with polymerization-induced self-assembly (PISA), generating vesicle, multicompartment micelle (MCM), and core-compartmentalized worm (CCW), where PEG, PVL, and PGMA are poly(ethylene glycol) monomethyl ether, poly(δ-valerolactone), and poly(glycidyl methacrylate) and PGMA is grown during the PISA. MCM and CCW are uniquely obtainable using terpolymers. The PVL segment is biodegradable, and the obtained assemblies are bio-decomposable. Heavy metal-free and sulfur-free synthesis and bio-decomposability of the assemblies are attractive features.